The Fr. José Maurício Nunes Garcia's Modinhas: sources, edition and practice (Per Musi, 2019)
The Fr. José Maurício Nunes Garcia (1767-1830) is one of the most important Brazilian composers in the first half of the 19th century. This article presents the modinhas composed by him, indicating the location of the oldest scores and offering his modern edition - one of these songs, titled Estas lágrimas sentidas, had his manuscript recently identified by this author. The present text also offers some subsidies for the execution of these modinhas, facilitating the access and the interpretation of the repertoire by both Brazilians and foreign singers. This is intended to be an important contribution to the task of deconstructing, or overcoming, the somewhat condescending or disinterested stance of some interpreters and researchers when talking about modinha specifically.